An Investigation Metonymy in English and Vietnamese Short Stories - Trịnh Ngọc Xuân Thảo (2009)
In the era of worldwide cooperation and integration, communicating in English, an international language, has become an indispensable demand to most people. The communication can be carried out in many ways, of which ….